Визначення економіко-технологічних інструментів оптимізації діяльності авіакомпанії при мультимодальній доставці негабаритних вантажів - Литвиненко, С. Л.; Литвиненко, Л. Л. (Видавництво Львівської політехніки, 2018)
Проаналізовано існуючі наукові дослідження щодо проблеми мультимодальної доставки негабаритних вантажів, встановлено, що доставка негабаритних вантажів особливо складної конструкції передбачає складання комплексного проекту. Детально охарактеризовано приклади доставки унікальних негабаритних вантажів за участю авіаційного транспорту та визначено умови перетворення авіаційного перевізника у логістичного 3PL провайдера. Дано визначення поняття “гібридна бізнес-модель вантажного авіаперевізника” та наголошено на недопущенні розриву між пропозицією і очікуваннями вантажної клієнтури.

Historical preconditions for the formation of the oversized air transportation market, change of the logistic delivery chain, which is connected with determined prerequisites, and current trends in the organization of logistics management of oversized cargoes’ delivery in multimodal connection were analysed. Previous scientific researches concerning the solution of the problem of multimodal delivery of oversized cargoes were studied, and despite comprehensive analysis of the mentioned problem, its part connected with the development of the toolkit for optimization of the air carrier’s activity in the case of multimodal delivery of oversized cargoes remains unresolved. Consequently, the authors determined the need to determine preconditions for the creation of economic and technological tools for optimizing the airline’s activity in the multimodal delivery of oversized cargoes in terms of transformational changes in the economy as the purpose of the article. Delivery of oversized cargoes of an especially complex design involves the preparation of a comprehensive project. The authors analysed the most complex and interesting examples of delivery of unique oversized cargoes with the participation of air transport. First of all, these examples were related to: non-separable delivery of cargoes with special protruding elements; creation of a special ramp loading system by the air carrier, which allows it to be used in the transportation of long-range oversized cargoes in the future, including those for the aerospace industry; designing two special transport frameworks using 3D-modelling, which allowed loading the tower into an airplane by means of external cranes over the trestle and rails; delivery of two wing consoles with designing of loading schemes using CATIA, a special system of 3D modelling, etc. The authors emphasized that no delivery of oversized cargoes with the participation of air transport is possible without the participation of at least road transport, which provides delivery to and from the airport. It was noted that most often the airline used the services of specialized companies engaged in the organization of logistics schemes for the delivery of oversized cargoes using air transport, which is not entirely justified in terms of simplification of the delivery process, but is not optimal in view of maximizing its own financial benefits. It was outlined that the air carrier of oversized cargoes may both act as a participant of the element in the multimodal delivery chain by air transport and take on the role of an organizer of the entire chain on the door-to-door principle, becoming the basic 3PL provider. It requires the development of a number of theoretical and methodological tools, in particular the identifying of conceptual levels of hybridization of the business model of a cargo air carrier, as well as the solution of the multicriteria task of optimizing the airline’s production and logistics activities in conditions of changing internal and external environments. The definition of “hybrid business model of a cargo air carrier” was given and the emphasis on avoiding the gap between the offer and the expectations of the cargo clientele was placed.
Determination of economic and technological tools for optimization of airline’s activity in multimodal delivery of oversized cargoes
Keywords: логістичне управління; доставка вантажів; мультимодальна доставка; чартерний рейс; унікальний негабаритний вантаж; logistics management; cargo delivery; multimodal transportation; charter flight; unique oversized cargo; 338.47